Experimental Study on the Influence of Particle Diameter, Mass Concentration, and Impeller Material on the Wear Performance of Solid–Liquid Two-Phase Centrifugal Pump Blade - Wang, Yanping; Li, Weiqin; He, Tielin; Liu, Hao; Han, Chuanfeng; Zhu, Zucao (Frontiers in Energy Research, 2022)
A centrifugal pump is an important solid–liquid mixture conveying machinery, which is widely used in mineral mining, water conservancy engineering, and other fields. Solid particles will wear the impeller of the centrifugal pump in the process of transportation, resulting in lower service life of the impeller, especially in the transportation of a high concentration of solid particles. Many scholars use numerical simulation to study the wear of centrifugal pumps, but few efforts have been made in the wear experiment. In this study, the effect of three factors, namely, diameter of solid particles, mass concentration of particles, and material of impellers on the wear of a solid–liquid two-phase centrifugal pump was studied by the wear experiment. The solid particles are SiO2 with irregular shapes, and the diameter ranges are 0.125–0.212 mm, 0.212–0.425 mm, and 0.425–0.710 mm. The mass concentration of solid particles is 15%, 20%, and 30%. The material of impellers is carbon structural steel (Q235), gray cast iron (HT200), and low-alloy high-strength steel (16 Mn). The amount of wear is determined by measuring the thickness of the impeller material before and after wear experiments. The wear morphology of the impeller was observed by using a digital microscope. The results showed that the wear mainly concentrated on the middle and trailing edges of the blade. Impellers of different materials suffer different wear forms, among which the impeller made of HT200 has the best erosion resistance. The increase of solid mass concentration will aggravate the wear of the impeller. The change of particle diameters also has a great influence on impeller wear.